Distribution of constitutive heterochromatin in species of triatomines with fragmentation of sex chromosomes X - Guerra, A.L. [UNESP]; Alevi, K.C.C. [UNESP]; Rosa, J.A. [UNESP]; Oliveira, Maria Tercilia Vilela de Azeredo [UNESP] (Genetics and Molecular Research, 2014)
Cytogenetic analyses of triatomines are considered to be important taxonomic tools. Thus, we analyzed the pattern of constitutive heterochromatin in 7 species of triatomine with fragmentation of the sex chromosome X, focusing on the cytotaxonomy of these triatomines. The species analyzed included Triatoma vitticeps, Triatoma melanocephala, Triatoma tibiamaculata, Triatoma protracta, Meccus pallidipennis, Panstrongylus megistus, and Panstrongylus lignarius. The seminiferous tubules of the adult males were subjected to C-banding. P. megistus and P. lignarius showed differences in chromosome number and disposition of constitutive heterochromatin, as only P. lignarius showed C-blocks in autosomes. C-banding can differentiate these species, since one of the sex chromosome (X) is heterochromatic in T. vitticeps. T. protracta showed C-blocks in both ends of all autosomes, T. tibiamaculata showed terminal C-dots in some autosomal pairs and M. pallidipennis did not show constitutive heterochromatin in autosomes. Thus, we confirmed the heterochromatic pattern of 7 species of insects and emphasized the importance of cytogenetic techniques for C-banding for taxonomy studies of the triatomines, which are important vectors of Chagas disease.
Keywords: C-banding; Cytotaxonomy; Triatominae